2008
DOI: 10.1614/ws-07-130.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Vigor and Ozone Response in Horseweed (Conyza Canadensis) Biotypes Differing in Glyphosate Resistance

Abstract: Horseweed has become increasingly difficult to control in the San Joaquin Valley (SJV) of California. Resistance to glyphosate may not fully explain the quasi-invasive behavior of this native species. We contrast glyphosate-resistant (GR) and glyphosate-susceptible (GS) horseweed biotypes for vigor during the vegetative stage and for resistance to ozone (O3). The SJV is impacted by O3 air pollution, which could be a factor in competitiveness of GR vs. GS. Both biotypes were exposed during the seedling and vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 48 publications
7
48
3
Order By: Relevance
“…In contrast, at low O 3 , GS exhibited about 50% damaged leaf area at 46 DAP, increasing to about 70% by 53 DAP (Figure 3a). This contrasted with very low baseline levels (0 to 5%) of injury in both biotypes observed at low O 3 in the absence of glyphosate (Grantz et al 2008).…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…In contrast, at low O 3 , GS exhibited about 50% damaged leaf area at 46 DAP, increasing to about 70% by 53 DAP (Figure 3a). This contrasted with very low baseline levels (0 to 5%) of injury in both biotypes observed at low O 3 in the absence of glyphosate (Grantz et al 2008).…”
Section: Resultscontrasting
confidence: 63%
“…The resulting R/S ratio at low O 3 was much greater in GS (Figure 4b). In contrast, in the absence of glyphosate (Grantz et al 2008) R/S was considerably greater in GR.…”
Section: Resultsmentioning
confidence: 78%
“…The same authors reported also the largest capacity of GR plants to accumulate dry mass even in conditions of water deficit. C. canadensis plants resistant to glyphosate under stress conditions of ozone also produced about 40% more biomass compared to susceptible biotypes (Grantz et al 2008). However, studies carried out by Moreira et al (2010) with GR and GS biotypes of C. canadensis and C. bonariensis demonstrated lesser amount of dry mass in any resistant biotype, indicating a negative effect on the ability of development of resistant plants.…”
Section: Growth Phenological and Seed Developmentmentioning
confidence: 94%
“…Also, C. canadensis plants started to elongate the main stem earlier in the GR than in the GS biotype (Grantz et al 2008;Shrestha et al 2010). The growth in height is a feature related to competitiveness, where plants with fast development tend to shade the environment, reducing the availability of light and suppressing the smaller plants (Balbinot Junior et al 2003).…”
Section: Growth Phenological and Seed Developmentmentioning
confidence: 99%
See 1 more Smart Citation